Sol–gel chemistry mediated Zn/Al-based complex dispersant for SWCNT in water without foam formation. (November 2015) - Kukobat, Radovan; Minami, Daiki; Hayashi, Takuya; Hattori, Yoshiyuki; Matsuda, Takafumi; Sunaga, Motoo; Bharti, Bhuvnesh; Asakura, Kiyotaka; Kaneko, Katsumi
Abstract: We report a bimetallic Zn/Al complex as an efficient inorganic dispersant for SWCNT, synthesized from Zn(CH3 COO)2 and Al(NO3 )3 . The Zn/Al complex shows more than four times greater efficiency at dispersing SWCNT than widely used surfactants (CTAB and SDS). Besides remarkable dispersibility, the Zn/Al complex does not foam upon any shaking treatment and it can be used just after quick dissolution of the powdered form, which is a marked advantage over surfactants. The Zn/Al complex, containing amorphous Al(CH3 COO)3 and a complex of Zn 2+ and NO3 − ions, should have a unique dispersion mechanism, differing from the surfactants. Al(CH3 COO)3 has higher affinity for SWCNT than ions, adsorbing onto its surface in the first layer and attracting Zn 2+ and NO3 − ions. Charge transfer interactions between the Zn/Al complex and SWCNT, as evidenced by optical absorption spectroscopy, should induce a charge on SWCNT; the zeta potential of such coated SWCNT was +55 mV, indicating a high dispersion stability in aqueous media. Hence, the Zn/Al complex can widen the applications of SWCNT to various technologies such as the transparent and conductive films, as well as high performance composite polymers.